ANALISIS BREAK EVEN POINT HASIL PELEDAKAN BATU GRANIT PADA UNIT PELEDAKAN PT ADITYA BUANA INTER DI KECAMATAN MERAWANG KABUPATEN BANGKA - Vikram Rinaldi; E.P.S.B Taman Tono; Irvani Irvani (MINERAL, 2019)
The process of mining granite in PT Aditya Buana Inter is mined with an open pit (quarry)system. The granite blasting system at PT Aditya Buana Inter consisted of 5 blasting and with 386holes of explosive holes obtained, the total institutional volume was 199.996 m3 (BCM) and the totalvolume of blasting was 13001, 7 m3 (BCM) of the target company of 16,000 m3 (BCM) / month. Drillingand blasting activities to produce blasting volumes of course there are factors that influence theseactivities. Factors that influence drilling and blasting activities affect the costs incurred and the volumeof blasting results produced, the factors that influence these activities include: weather, frontconditions, equipment damage, less optimal blasting geometry measurements. The activity is certainlynot inseparable from the costs that must be incurred by PT Aditya Buana Inter both fixed costs andvariable costs. The total costs incurred by PT Aditya Buana Inter on September 2, 2018 to October4, 2018 are Rp 352,677,200.00 which includes fixed costs of Rp 170,616,020.00 and variable costs(variable costs) of Rp 182,061,000.00, and variable costs per m3 the volume of blasting yield is Rp14,003 /m3. Break even points obtained from calculations for units are 812,468 m3 and in rupiah Rp181,992,901.00. PT Aditya Buana Inter income from the sale of split stone is Rp 472,846,080.00obtained from the sales volume of 2110.92 m3 with a selling price of Rp 224,000 /m3, the profit (L)obtained is Rp 90,610,140.00. Calculation of Break Even Point analysis can determine the minimumamount of volume of rock from the blasting that will be produced and to find out the condition of thecompany not making a profit and also not losing.